Implementasi Budaya 5R di Lembaga Pemerintah K Jakarta - Suyadi; Chintia Liliana (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study aimed to determine the implementation of the 5R culture (Ringkas, Rapi, Resik, Rawat, Rajin /simple, neat, clean, conscious, industrious) at a branch of government office at Jakarta, as a part of a Ministrial General Directorate. This research uses descriptive qualitative methods. The data sources from 3 informants consisting of the a lower level manager and two staffs. The data collected by observation, interviews, analysis of documentation, and triangulation techniques. The research concluded that 5R culture implemented by the actions of the principles of 5R at the job environment. The implementation stimulated the planned organizational target at work: efficiency, productivity, quality, and work safety. One R that did not implemented clearly is the discipline. Some staffs still came late to the office. Keywords: Implementation of Work Culture, Qualitative Method, 5R Culture